2015
DOI: 10.1074/jbc.m114.626705
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repressor TrmBL2 from Thermococcus kodakarensis Forms Filamentous Nucleoprotein Structures and Competes with Histones for DNA Binding in a Salt- and DNA Supercoiling-dependent Manner

Abstract: Background: TrmBL2 and histones maintain the genome functioning in hyperthermophilic euryarchaeal cells. Results: TrmBL2 forms filaments on DNA through cooperative binding and competes with histones in a salt-and DNA supercoiling-dependent manner. Conclusion: TrmBL2-histone collective behavior dynamically controls DNA organization. Significance: The discovered mechanisms provide insights into the regulation of the genome structure and global transcription profile by TrmBL2 and histones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 64 publications
4
34
0
Order By: Relevance
“…To demonstrate practical utility of the transfer-matrix formalism, in this section we describe how to exploit it in order to extract valuable information about DNAprotein interactions from experimentally measured forceextension curves of DNA. For this purpose, we use experimental data obtained on a torsionally relaxed 48,502 bp λ-DNA incubated in the presence of different amounts of TrmBL2 protein in solution [33].…”
Section: F Application Of the Transfer-matrix Theory For Processing mentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate practical utility of the transfer-matrix formalism, in this section we describe how to exploit it in order to extract valuable information about DNAprotein interactions from experimentally measured forceextension curves of DNA. For this purpose, we use experimental data obtained on a torsionally relaxed 48,502 bp λ-DNA incubated in the presence of different amounts of TrmBL2 protein in solution [33].…”
Section: F Application Of the Transfer-matrix Theory For Processing mentioning
confidence: 99%
“…[4][5][6][7][8][9]), that generate stretching and twisting forces on the chromosomal DNA [10][11][12][13][14][15]. It is also known that chromosomes form extensive adhesion contacts with a number of nuclear membrane proteins, establishing force-transmitting links between the chro-plexes (such as eukaryotic/archaeal histones) [23,24,35]; 2) DNA-bending proteins, which sharply curve DNA at the protein binding site (like bacterial HU, IHF and Fis) [22, 25-28, 30, 32, 36]; 3) DNA-bridging proteins that cross-link DNA duplexes (for example, bacterial H-NS, human HMGA2, or any other protein that mediates DNA loops) [29,[37][38][39], and 4) DNA-stiffening proteins forming rigid nucleoprotein filaments along DNA (like archaeal TrmBL2 and Alba) [31,33,40]. Thus, the four major groups of DNA-architectural proteins form nucleoprotein complexes, which have very different 3D structures, leading to diverse responses of these proteins to force and torque constraints applied to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that TrmBL2 exhibits concentration-dependent, high-and low-affinity DNA binding modes that are influenced by the salt concentration of the medium. The study also demonstrates that nonspecific interactions of TrmBL2 with DNA backbone contribute significantly to the TrmBL2-DNA binding energy [9]. Together with archaeal histones [10] and Alba (acetylation lowers binding affinity) [10,11], TK0471/TrmBL2 is now considered to be a member of chromosome structuring proteins in archaea [12].…”
Section: Introductionmentioning
confidence: 80%
“…2a). Moreover, it is maintained at a high level of 37 μM in T. kodakarensis cells [9]. Band shift experiments revealed that it binds to the TGM sequence with low affinity but not exclusively [3].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation